Organizational Justice, Psychological Empowerment, dan Organizational Commitment: Mediasi Person-Organization Fit - Agustina Inesia Emasintia Sutoro Sutoro; Retno Dwiyanti; Ugung Dwi Ario Wibowo; Hazalizah binti Hamzah (Fakultas of Psychology, Universitas Muria Kudus, 2026)
The retail industry has become one of the business sectors that has experienced remarkable progress in the last five years. However, retail companies still face challenges related to organizational commitment, as reflected in relatively high employee turnover rates. This study aims to analyze the effects of organizational justice and psychological empowerment on organizational commitment through the mediating role of person–organization fit among retail employees. The participants were 318 store crew members from a retail company located in Cilacap Regency, Central Java, Indonesia. A purposive sampling technique was used. This study employed a quantitative survey approach, and data were analyzed using SEM-PLS with SmartPLS 4.0. The results show that organizational justice has a positive and significant effect on organizational commitment, both directly and indirectly through person–organization fit. Organizational justice also significantly influences person–organization fit, and person–organization fit significantly affects organizational commitment. In contrast, psychological empowerment does not significantly influence organizational commitment or person–organization fit, and person–organization fit does not mediate the relationship between psychological empowerment and organizational commitment. These findings suggest that organizations should prioritize justice in policies and practices and strengthen value alignment between employees and the organization to enhance organizational commitment. Industri ritel menjadi salah satu sektor bisnis yang mengalami kemajuan signifikan dalam lima tahun terakhir. Namun, dalam praktiknya, perusahaan ritel masih memiliki sedikit masalah dalam hal komitmen organisasi dilihat dari tingkat turnover karyawan yang terbilang masih cukup tinggi. Penelitian ini bertujuan menganalisis pengaruh organizational justice serta psychological empowerment terhadap organizational commitment melalui peran mediasi person–organization fit pada karyawan ritel. Subjek penelitian adalah 318 crew store dari salah satu perusahaan ritel di Indonesia yang berlokasi di Kabupaten Cilacap, Jawa Tengah dipilih dengan teknik purposive sampling. Penelitian memanfaatkan pendekatan kuantitatif dengan metode survei serta analisis data dengan SEM-PLS melalui SmartPLS 4.0. Hasil analisis memperlihatkan bahwa organizational justice secara positif serta signifikan memengaruhi organizational commitment, baik secara langsung serta melalui mediasi person–organization fit. organizational justice juga berpengaruh signifikan terhadap person–organization fit, serta person–organization fit berpengaruh signifikan terhadap organizational commitment. Sebaliknya, psychological empowerment tidak signifikan memengaruhi organizational commitment maupun person–organization fit, dan person–organization fit tidak memediasi hubungan antara psychological empowerment dan organizational commitment. Penelitian ini memberikan implikasi praktis bahwa organisasi perlu lebih memfokuskan strategi pengelolaan karyawan mereka pada penguatan keadilan dalam kebijakan dan praktik organisasi serta membangun keselarasan nilai antara karyawan dan organisasi.